2021
DOI: 10.1029/2021ja029834
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Whistler Mode Waves and Electron Beam‐Like Distribution: Test Particle Simulations and THEMIS Observations

Abstract: The beam‐like electron population is often observed along with whistler mode waves in the Earth's magnetosphere, but its generation mechanism is still under debate. In this study, we use a test particle simulation model to study the Landau resonance between whistler mode waves and electrons, and quantify the proportion nb/nh of beam‐like electrons. There is a trend that the nb/nh first increases and then decreases with the increasing temperature of hot electrons or ratio of plasma frequency to electron gyrofre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, such very oblique waves are mainly associated with electron distributions having a plateau or weak field-aligned beams around the Landau resonant energy at the equator (Li, Mourenas, et al, 2016;R. Chen et al, 2019;Kong et al, 2021). Figure 4c shows that THEMIS E measured such a plateau both in the field-aligned and transverse phase space densities during the entire interval of whistler-mode wave observations (note also a weak field-aligned anisotropy of ∼1-5 keV electrons in Figure 4b).…”
Section: Themis Elfin and Dmsp Observations On 2021-01-01mentioning
confidence: 85%
See 1 more Smart Citation
“…Accordingly, such very oblique waves are mainly associated with electron distributions having a plateau or weak field-aligned beams around the Landau resonant energy at the equator (Li, Mourenas, et al, 2016;R. Chen et al, 2019;Kong et al, 2021). Figure 4c shows that THEMIS E measured such a plateau both in the field-aligned and transverse phase space densities during the entire interval of whistler-mode wave observations (note also a weak field-aligned anisotropy of ∼1-5 keV electrons in Figure 4b).…”
Section: Themis Elfin and Dmsp Observations On 2021-01-01mentioning
confidence: 85%
“…For typical electron distributions with a smoothly decreasing density toward higher parallel electron energy, Landau damping by these dense suprathermal electrons would quickly reduce the wave intensity to the noise level (Kennel, 1966; Bortnik et al., 2007; L. Chen et al., 2013). Accordingly, such very oblique waves are mainly associated with electron distributions having a plateau or weak field‐aligned beams around the Landau resonant energy at the equator (Li, Mourenas, et al., 2016; R. Chen et al., 2019; Artemyev & Mourenas, 2020; Kong et al., 2021). Figure 4c shows that THEMIS E measured such a plateau both in the field‐aligned and transverse phase space densities during the entire interval of whistler‐mode wave observations (note also a weak field‐aligned anisotropy of ∼1–5 keV electrons in Figure 4b).…”
Section: Themis Elfin and Dmsp Observations On 2021‐01‐01mentioning
confidence: 99%
“…The cold electron component is not considered, because its thermal velocity is much lower than 0.5 V Ae . Since electron plateau components along with chorus waves are typically observed at ∼0.5 V Ae (Chen et al., 2019; Kong et al., 2021; Li et al., 2019; Min et al., 2014), then the v b is determined by the positive gradient of PSD in the range of 0.4–0.6 V Ae (Min et al., 2014). In Event I, v b = 0.431 V Ae in both directions.…”
Section: Observational Resultsmentioning
confidence: 99%
“…Their number densities are estimated as n p /n 0 ∼ 10 −3 , consistent with those in banded chorus events from observations (Figures 2d and 2f). In the magnetosphere, the plateau components are commonly observed along with chorus waves (Chen et al, 2019;Kong et al, 2021;Li et al, 2019;Li, Mourenas, et al, 2016;Min et al, 2014). With THEMIS data, Min et al (2014) have suggested that the bulk velocities of plateau components generally match the Landau resonant velocities of chorus waves, indicating these components are formed due to Landau resonance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation